Comparação da atividade repelente de dois derivados à base de ácido lático e de um repelente comercial em fêmeas de Aedes aegypti (linnaeus, 1762) (Diptera:Culicidae) - Cabral, Victória Oliveira (Brasil, 2025)
The Aedes aegypti mosquito has been causing significant public health problems worldwide by transmitting pathogens responsible for various arboviral diseases. To reduce the number of cases or prevent these diseases, control methods are employed. In addition to these methods, one way to minimize human contact with the vector is using repellents. Based on this, the Department of Chemistry at the Federal University of Paraná (UFPR) developed and produced derivatives based on lactic acid, which, in partnership with the Malaria and Dengue Laboratory (LMD), evaluated the repellent activity of two derivatives, their protection time, and their effectiveness compared to a commercial repellent used as a control. The evaluation of repellent activity began with a negative test, which was necessary to observe the volunteer's attractiveness and the activity of the female mosquitoes. After the negative test, 1g of commercial repellent (25% DEET) was applied to the back of the right hand, while a dilution of 1mL (100 µL of the derivative diluted in 900 µL of PA Ethanol) was applied to the back of the left hand. After application, the products were allowed to evaporate, and then nitrile gloves with a 3x3 cm cut were worn. Two cages were used (control and test), each containing 30 female A. aegypti mosquitoes, aged 3 to 9 days, without prior blood feeding. The evaluation consisted of observing whether the mosquitoes attempted to bite the hand or landed for more than five seconds. If this occurred, the test was immediately interrupted and considered a failure of repellency. Otherwise, after three minutes, repellency was confirmed. Thus, the efficacy and protection percentage of the derivatives and controls were assessed. The results indicate that both derivatives exhibited repellent activity, providing over 8 hours of protection. These findings suggest the potential for developing new commercial repellents to prevent bites from female A. aegypti mosquitoes.